Frontiers in Ovarian Cancer Science - Katabuchi, Hidetaka (Springer Singapore : Imprint: Springer, 2017)
This volume presents the latest advances and the current status of our understanding regarding ovarian cancer, addressing both the basic and clinical aspects of the disease. In terms of basic medicine, the WHO Classification of Tumors of Female Reproductive Organs was revised in 2014, and that version addresses several new concepts and histopathological classifications not previously included. One of the most revolutionary breakthroughs concerns the genesis of epithelial ovarian tumors, shifting the focus from the ovarian surface epithelium to serous tubal intraepithelial carcinomas. Clinically, the mortality rate of epithelial ovarian cancer has gradually increased over the past few decades, making it essential to pursue multidisciplinary treatment and apply novel techniques such as neoadjuvant chemotherapy in daily clinical practice. The primary clinical task is the effective treatment of recurrent ovarian cancer with early palliative medicine. Fertility-sparing surgery may also be pursued depending on histologic subtypes, stage, extent of disease, and preexisting ovarian reserve with the concept of oncofertility. On the basis of the considerations described above, each expert author elucidates the science of ovarian cancer in detail, thus providing a collection that will benefit young medical oncologists and seasoned gynecologists and obstetricians alike.
Keywords: Medicine.; Gynecology.; Oncology.; Reproductive medicine.; elektronické knihy; electronic books